Technical Diagnostics of Building Structures (Czech Journal of Multidisciplinary Innovations, 2022)
Technical diagnostics is one of the elements of the general theory of building reliability. Assessment of the state of structures at various stages of the operation of buildings establishes the signs and causes of damage, allows you to identify defects in collapsing structures, determine the degree and boundaries of damage in order to repair them in a timely and high-quality manner. Defects and damage can be classified according to the causes of occurrence, conditions of occurrence, external signs, the degree of influence on performance. Diagnostics is one of the elements of the general theory of the reliability and durability of buildings, its specific tasks are related to the early detection of defects and structural failures.